PENERAPAN STRATEGI MOTIVASI ARCS DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII-7 SMP NEGERI 8 PEKANBARU - ', Juliana; ', Syofni; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was based on the students achievement in learning mathematics especially grade VIII-7 SMP Negeri 8 Pekanbaru the Mastery Minimum Criteria with percentage of 14,6% on the test about Tribe Factorization Algebra. This research is a class action research. This research aims to improve learning result in mathematics in grade by implementation of ARCS Motivation Strategy in Cooperative Learning Model STAD. ARCS Strategy is a strategy that was developed based on a review of the motivation with the aim to enable students to learn. This study aims to determine the completeness of student learning, attention , relevance of teaching materials to students' needs , confidence and satisfaction of the students on the material equation of a straight line. The subject of this research were the students in the class VIII-7 SMP Negeri 8 Pekanbaru that consist of 16 boys and 26 girls at the first semester of academic year 2016/2017. The instruments of data collection in this research were observation sheets and student’s mathematic tests. The observation sheets were analyzed in statistic desciptive. The results of this research showed an increasing number of students learning mathematic from the basic score with percentage 14,6% to 47,6% on the first test and 78,5% on second test. The frequency distribution analysis as well showed an improvement student achievement are increasing the number of student who received higher criteria on the first test and second test compared the number of student who received higher criteria on the basic score. On the low criteria, the number of student at interval 21–40 descreased from basic score to the first test and second test. Furtehrmore, on the higher criteria, the number of student at interval 81-100 increased from basic score to first test with 4 students into 10 students, then have increased on the second test with 23 students. Based on the result of this research could be concluded that the implementation of ARCS Motivation Strategy in Cooperative Learning Model STAD) improve the student’s achievement of learning mathematic in grade VIII-7 SMP Negeri 8 Pekanbaru in the first semester academic years 2016/2017.